Polyphenol-mediated microbiome modulation in STEMI patients: a pilot study - Argul Issilbayeva; Shynggys Sergazy; Azamat Zhashkeyev; Alexandr Gulyayev; Samat Kozhakhmetov; Zarina Shulgau; Madiyar Nurgaziyev; Ayaulym Nurgaziyeva; Sanzhar Zhetkenev; Nurislam Mukhanbetzhanov; Zharkyn Jarmukhanov; Zhanel Mukhanbetzhanova; et al. (Frontiers in Medicine)
IntroductionThis study investigates the effects of polyphenol supplementation on gut microbiome composition and cardiovascular health in patients with ST-segment elevation myocardial infarction (STEMI).MethodsDouble-blind randomized control trial where participants received either polyphenol supplementation or placebo for 3 months, after which composition of the gut microbiome; clinical and laboratory parameters, including TMAO levels and oxidative stress levels, were assessed.ResultsThe stable TMAO levels (from 0.5 [0.2–0.9] to 0.4 [0.3–0.9] μmol, p > 0.05) were observed in the polyphenol group, compared to the increase observed in the placebo group (from 0.5 [0.3–0.6] to 0.7 [0.5–1.4] μmol, p < 0.001). Polyphenol supplementation significantly decreased the Firmicutes/Bacteroidetes ratio (p = 0.04) and increased beneficial bacteria such as Roseburia (p = 0.01), Agathobaculum sp. (p = 0.004), Alistipes finegoldii (p = 0.04) and Sellimonas (p = 0.002). Predicted metabolic pathways analysis supports potential mechanisms linking polyphenol intake to microbiome modulation and TMAO regulation.ConclusionOur findings demonstrate that polyphenol supplementation maintains stable TMAO levels by restructuring gut microbiome composition in STEMI patients, evidenced by a more focused microbiome with a significant increase in beneficial butyrate-producing bacteria (Roseburia, Agathobaculum sp., Alistipes finegoldii, and Sellimonas) and a decreased Firmicutes/Bacteroidetes ratio, suggesting microbiome-mediated cardioprotective effects. While promising,l our preliminary findings require further studies with larger cohorts and more advanced sequencing methods to establish their significance for cardiovascular health.Clinical trial registrationClinicalTrial.gov, identfier: NCT06573892.